Tekoeté = Manera auténtica de ser - Gamarra, Hugo (Ara Films Producciones, 2010)
A social and cultural testimony of Paraguayan peasant life (in the indigenous language of Paraguay: the Guarani), its subsistence problems, the emigration of family members, their struggles for the recognition of their rights, their relationship with nature and their hopes. This testimony corresponds to the shared experience with the Ramos Gómez family, resident of Cordillerita Costa, Ybycuí, Department of Paraguarí, 120 kms. of the capital Asunción, on April 20, 2008, national election day. --